Brothers and keepers - Wideman, John Edgar (Holt, Rinehart and Winston, 1984)
A haunting portrait of lives arriving at different destinies, Brothers and Keepers is John Edgar Wideman’s seminal memoir about two brothers — one an award-winning novelist, the other a fugitive wanted for robbery and murder. Wideman recalls the capture of his younger brother Robby, details the subsequent trials that resulted in a sentence of life in prison, and provides vivid views of the American prison system. A gripping, unsettling account, Brothers and Keepers weighs the bonds of blood, tenderness, and guilt that connect Wideman to his brother and measures the distance that lies between them.